In Geneva. From: L'Humanité nouvelle, Paris, Mars 1900, P. 280. F.l.t.r.: Monchal, Perron, Bakunin, Fanelli and Mroczkowski - Chevalier, A.,
In Geneva. From: L'Humanité nouvelle, Paris, Mars 1900, P. 280. F.l.t.r.: Monchal, Perron, Bakunin, Fanelli and Mroczkowski.